2019
DOI: 10.1073/pnas.1814512116
|View full text |Cite
|
Sign up to set email alerts
|

Near-continuously synthesized leading strands in Escherichia coli are broken by ribonucleotide excision

Abstract: In vitro, purified replisomes drive model replication forks to synthesize continuous leading strands, even without ligase, supporting the semidiscontinuous model of DNA replication. However, nascent replication intermediates isolated from ligase-deficient Escherichia coli comprise only short (on average 1.2-kb) Okazaki fragments. It was long suspected that cells replicate their chromosomal DNA by the semidiscontinuous mode observed in vitro but that, in vivo, the nascent leading strand was artifactually fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…A recent study has revisited the questions surrounding the origin of replication intermediates in bacteria ( 81 ). Surprisingly, nearly all of the LMW leading strand products observed in earlier studies can be explained by fragmentation as part of excision-repair processes.…”
Section: Introduction: the Eukaryotic Dna Replication Machinerymentioning
confidence: 99%
“…A recent study has revisited the questions surrounding the origin of replication intermediates in bacteria ( 81 ). Surprisingly, nearly all of the LMW leading strand products observed in earlier studies can be explained by fragmentation as part of excision-repair processes.…”
Section: Introduction: the Eukaryotic Dna Replication Machinerymentioning
confidence: 99%
“…If RNase H2 is unable to remove these ribonucleotides (19), they can have both favorable (20,21) and lethal biological consequences (22). Recent investigations have shown that ribonucleotides are deleterious lesions that can lead to mutations, large deletions, replication stress, strand breaks (topoisomerase-1 mediated repair), chromosomal rearrangements, loss of hereditary information, and disruption of transcription processes (1,(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility for the retention of the backbone sugars of RNA within DNA is the incomplete removal of stretches of RNA from Okazaki fragments during genome duplication (12). In Escherichia coli, ribonucleotides can increase the leading strand fragmentation during the replication process (19). The presence of ribonucleotides in DNA has been linked to systemic autoimmunity (20).…”
mentioning
confidence: 99%